The anatomy of COVID‐19‐related conspiracy beliefs: Exploring their nomological network on a nationally representative sample - Knežević, Goran; Lazarević, Ljiljana B.; Mihić, Ljiljana; Milovančević, Milica Pejović; Terzić, Zorica; Tošković, Oliver; Vuković, Olivera; Todorović, Jovana; Marić, Nađa P. (British journal of clinical psychology, 2023)
Objectives The outbreak of the COVID‐19 pandemic was followed by the widespread proliferation of conspiracy beliefs (CBs) regarding the origin and harmfulness of the virus and a high level of hesitancy to vaccinate. We aimed to test a series of hypotheses on the correlates of CBs and vaccination, including socio‐demographic factors, personality dispositions, somatic health, stressful experiences during pandemics, and psychological distress. Method The sample (N = 1203), was based on a multistage probabilistic household sampling representative of the general population. The subjects were randomly split into two approximately equal subgroups, enabling cross‐validation. Based on the findings in the exploratory, the SEM model was tested in the confirmatory subsample. Results The correlates of CBs were Disintegration (proneness to psychotic‐like experiences), low Openness, lower education, Extraversion, living in a smaller settlement and being employed. The correlates of vaccination were older age, CBs and larger places of living. Evidence on the role of stressful experiences and psychological distress in CBs/vaccination was not found. The findings of moderately strong and robust (cross‐validated) paths, leading from Disintegration to CBs and from CBs to vaccination were the most important ones. Discussion Conspiratorial thinking tendencies—related to health‐related behaviour such as vaccination—appear to be, to a considerable extent, manifestations of the mechanisms that are part of our stable, broad, trait‐like thinking/emotional/motivational/behavioural tendencies, primarily proneness to psychotic‐like experiences & behaviours.